Estimation of local anisotropy of plexiform bone: Comparison between depth sensing micro-indentation and Reference Point Indentation - Dall'Ara, E.; Grabowski, P.; Zioupos, Peter; Viceconti, M. (Elsevier, 2015)
The recently developed Reference Point Indentation (RPI) allows the measurements of bone properties at the tissue level in vivo. The goal of this study was to compare the local anisotropic behaviour of bovine plexiform bone measured with depth sensing micro-indentation tests and with RPI. Fifteen plexiform bone specimens were extracted from a bovine femur and polished down to 0.05 µm alumina paste for indentations along the axial, radial and circumferential directions (N=5 per group). Twenty-four micro-indentations (2.5 µm in depth, 10% of them were excluded for testing problems) and four RPI-indentations (~50 µm in depth) were performed on each sample. The local indentation modulus Eind was found to be highest for the axial direction (24.3±2.5 GPa) compared to the one for the circumferential indentations (19% less stiff) and for the radial direction (30% less stiff). RPI measurements were also found to be dependent on indentation direction (p<0.001) with the exception of the Indentation Distance Increase (IDI) (p=0.173). In particular, the unloading slope US1 followed similar trends compared to the Eind: 0.47±0.03 N/µm for axial, 11% lower for circumferential and 17% lower for radial. Significant correlations were found between US1 and Eind (p=0.001; R2=0.58), while no significant relationship was found between IDI and any of the micro-indentation measurements (p>0.157). In conclusion some of the RPI measurements can provide information about local anisotropy but IDI cannot. Moreover, there is a linear relationship between most local mechanical properties measured with RPI and with micro-indentations, but IDI does not correlate with any micro-indentation measurements
Keywords: Bone; Reference Point Indentation; Micro-indentation; Anisotropy; Plexiform